Circum-menarcheal bone acquisition is stress-driven: A longitudinal study in adolescent female gymnasts and non-gymnasts - Troy, K. L.; Scerpella, T. A.; Dowthwaite, J. N. (Journal of Biomechanics, 2018)
Mechanical loading through youth exercise is highly modifiable and represents a strategy to maximize peak adult bone mass, with the potential for broad implementation across the population to lower fracture risk. For girls, circum-menarcheal growth is critical, with around 50% of adult bone acquired over a 4-year period. Here, we prospectively followed 10 gymnasts and 12 age-matched non-gymnasts across approximately 4 years circum-menarche. A combination of pQCT and subject-specific finite element models were used to measure differences in bone acquisition and structure between the groups, and to determine the degree to which specific mechanical factors predict change in bone structure. At baseline, gymnasts had stronger bone, including 26% higher BMC, 51% greater compressive strength, and 21% higher trabecular density. Over the study period, both groups more than doubled their bone strength. Pre-menarcheal principal stresses predicted change in pQCT variables for non-gymnasts, but not gymnasts. The bone of non-gymnasts became more asymmetrical than the bone of gymnasts. Our results suggest that exposure to the diverse, intense mechanical signals of gymnastic loading during adolescence imparts substantial benefits to bone geometry and mechanical function. Specifically, the bone of gymnasts is better able to resist loading from multiple directions, and operates with a higher factor of safety compared to non-gymnasts.